Influence Affiliate Marketing, Online Customer Review and Online Customer Rating on Shopee Consumers' Purchasing Decisions - Julia Sapitri; Mas Sridjoko Darodjatun; Lutfi Mohamad (Research Synergy Foundation, 2025)
The emergence of e-commerce has altered the way that consumers make judgments about what to buy. The purpose of this study is to examine how Shopee customers' purchase decisions are impacted by affiliate marketing, online customer reviews, and online customer ratings. In this work, the link between variables is analyzed quantitatively using a Structural Equation Modeling (SEM) methodology. 170 respondents who were active Shopee users were given a questionnaire as part of a survey to gather data. The analysis's findings demonstrate that consumer purchase decisions are positively and significantly impacted by affiliate marketing, online customer reviews, and online customer ratings.